Family Conflict Associated With Intrinsic Hippocampal-OFC Connectivity in Adolescent Depressive Disorder - Feng, Ruohan; Bao, Weijie; Zhuo, Lihua; Gao, Yingxue; Yao, Hongchao; Li, Yang; Liang, Lijun; Liang, Kaili; Zhou, Ming; Zhang, Lianqing; Huang, Guoping; Huang, Xiaoqi (Frontiers in Psychiatry, 2022)
Background: Family environment and life events have long been suggested to be associated with adolescent depression. The hippocampus plays a crucial role in the neural mechanism of major depressive disorder (MDD) through memory during stressful events. However, few studies have explored the exact neural mechanisms underlying these associations. Thus, the current study aimed to explore alterations in hippocampal functional connectivity (FC) in adolescent MDD based on resting-state functional magnetic resonance imaging and further investigate the relationship between hippocampal FC, environmental factors, and clinical symptom severity. Methods: Hippocampal FC was calculated using the seed-based approach with the bilateral hippocampus as the seed for 111 adolescents with and without MDD; comparisons were made between participants with MDD and controls. We applied the Family Environment Scale-Chinese Version (FES-CV) and Adolescents Self-Rating Life Events Checklist (ASLEC) to evaluate family environment and life stress. Their relationship with hippocampal FC alterations was also investigated. Results: We found that compared to controls, adolescents with MDD showed decreased connectivity between the left hippocampus and bilateral orbital frontal cortex (OFC) and right inferior temporal gyrus. In addition, the hippocampal-OFC connectivity was negatively correlated with conflict scores of the FES-CV in the MDD group and mediated the association between family conflict and depressive and anxiety symptoms. Conclusion: Our findings are novel in the field and demonstrate how family conflict contributes to MDD symptomatology through hippocampal-OFC connectivity; these findings may provide potential targets for personalized treatment strategies.